Trichoderma spp: Propagation, dosage and application in maize crop (Zea mays L.) - Cuenca Sedamanos, John Alberto; Quevedo Guerrero, José Nicasio; Tuz Guncay, Ivana Gabriela; Chabla Carillo , Julio Enrique (Universidad Pedagógica y Tecnológica de Colombia, 2022)
The use of Trichoderma spp. in organic agriculture is important due to its wide mode of action that includes: the segregation of secondary metabolites that induce the production of phytoalexins in plants and its antagonistic capacity, besides the antibiosis that cause the degradation of the cell walls of other pathogens inhibiting their development. The objective was to evaluate the effect of four strains of Trichoderma spp. on morphological parameters and yield of maize under field conditions. The research was conducted at the Technical University of Machala, Faculty of Agricultural Sciences, "Santa Inés" experimental farm. An experimental design of completely randomized blocks was used, 90 plants were evaluated per treatment, 4 treatments, 3 doses, 3 repetitions per dose, 10 plants per repetition in the variables previously mentioned, the treatments were: T1: Trichoderma asperellum; T2: Trichoderma melanomagnum; T3: Trichoderma spirale; T4: Trichoderma reesei in three doses. The results obtained indicate that the variables that presented statistical differences were: height of plant with T. spirale obtained 239,630 cm, number of leaves above the cob in T. melanomagnum and T. spirale were higher with 7,060 and 7,130 respectively, cob length in T. melanomagnum with 13,687 cm, cob diameter had similar values with the four strains, seed weight with T. melanomagnum obtained 59,410 g and seed moisture in T. asperellum with 26,933%. It's concluded that the strains T. asperellum and T. melanomagnum with doses x1010 and x1011 CFU obtained the best yields